Demographic characteristics of whole blood donors aged 56 to 60 in Guangzhou - Lei WU; Xuecheng DENG; Jieying YU; Yangfan DENG; Shijie LI (Zhongguo shuxue zazhi, 2022)
Objective To study the demographic characteristics of whole blood donors aged 56 to 60 in Guangzhou, so as to provide reference for smooth implementation of the recruitment and management of elderly blood donors in Guangzhou. Methods The data of whole blood donors, aged 56 to 60, in Guangzhou Blood Center from July 1, 2016 to June 30, 2021 were retrospectively analyzed, and such characteristics as the number of blood donations, gender, donation frequency, donation volume, occupation and educational background were analyzed. Results A total of 3 996 blood donors aged 56 to 60, including 3 013 males and 983 females, gave 14 416 donations during July 1, 2016 to June 30, 2021, with the proportion of 400 mL specification at 64.1% (6 999/10 918) of males, which was significantly higher than that of females 57.7% (2 017/3 498). The number of blood donors had been decreasing year by year, but the ratio of men to women was stable.The education background of blood donors were mainly high school, junior college, and undergraduate education, accounting for more than 60% in total, and the proportion of undergraduate and graduate degree trended to grow. Staff, workers, medical staff and civil servants were the majorities, and the proportion of medical staff trended to grow. Conclusion Male blood donors aged 56 to 60 in Guangzhou showed stronger intention to donate blood, and the proportion of blood donors with better education and medical staff was on the rise.